Beyond Bipolar: A Three-Dimensional Assessment of Monetary Frameworks - Kenneth N. Kuttner (Oesterreichische Nationalbank (OeNB), 2001)
A great deal of attention has been focused recently on the impact of exchange rate regimes, just as previous empirical research examined central bank autonomy and announced targets for domestic monetary policy. To date, however, these three elements of monetary frameworks have been assessed in isolation from one another, and all have been viewed in terms of a unidimensional spectrum of fixity versus flexibility. Using a newly-constructed dataset, this paper jointly analyzes and compares all three elements' effects on inflation and exchange rate behavior. The results show that each of the three elements has independent and distinct effects on nominal outcomes. Key findings include: (1) although hard pegs do tend to reduce inflation and attenuate exchange rate fluctuations within some range, they are clearly characterized by large devaluations; (2) central bank autonomy is associated with a more stable exchange rate and lower inflation; and (3) explicit inflation targeting reduces both inflation and its persistence, consistent with the view that inflation targeting increases flexibility through transparency. These results raise the possibility that a combination of central bank autonomy, inflation targeting, and a free float might offer the same benefits as any intermediate exchange rate regime on its own, without the proclivity to occasional large depreciations.
Keywords: E52; E61; F33; 330